Arabization During the Umayyad Dynasty - Alamsyah, Firdaus; Akmal, Royan; Virgani, Zahrina (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study aims to explore the Arabization movement that took place during the reign of the Umayyad Dynasty, with a primary focus on the rule of Caliph Abdul Malik ibn Marwan (41–132 AH / 661–750 CE). The objective is to describe the process and policies of Arabization implemented during this period, as well as its impact on Islamic civilization. This research employs a library research method to analyze sources such as historical books, scholarly articles, and ancient manuscripts, which are then processed using a content analysis approach. Based on the data analysis conducted, it can be concluded that the Arabization that occurred during the Umayyad Dynasty (41–132 AH / 661–750 CE) was the first comprehensive Arabization effort implemented across all conquered territories. The study reveals that language processing was a key aspect of Arabization, including the use of Arabic as the administrative language and the inscription of Arabic on coinage as a symbol of sovereignty. Although some regions continued to use their local languages, the Arabization policy was largely considered successful. The Arabization movement was executed through specific policies aimed at linguistic and cultural integration. This movement had significant sociocultural impacts on the groups involved, leading to both preferential treatment and discrimination by local communities and ruling officials. Eventually, the Umayyad Dynasty collapsed and was succeeded by the Abbasid Dynasty, which continued to uphold the Arabization policies.